Immunological signature of patients with thymic epithelial tumors and Good syndrome - Malfitano, Anna Maria; D’Esposito, Vittoria; De Placido, Pietro; Tortora, Marianna; Ottaviano, Margaret; Pietroluongo, Erica; Morra, Rocco; Mucci, Brigitta; Napolitano, Fabiana; Montella, Liliana; Giuliano, Mario; De Placido, Sabino; et al. (Frontiers in Immunology, 2022)
Background: Thymic epithelial tumors (TETs) are frequently accompanied by Good Syndrome (GS), a rare immunodeficiency, characterized by hypogammaglobulinemia and peripheral B cell lymphopenia. TETs can be also associated to other immunological disorders, both immunodeficiency and autoimmunity. Methods: In this study, we enrolled TET patients with GS to address differences between patients with or without associated autoimmune diseases (AD). We analyzed the immunophenotype from peripheral blood of these patients focusing on selected immune cell subsets (CD4+T cells, CD8+T cells, T regulatory cells, NK cells, B-cells, monocytes, eosinophils, basophils, neutrophils) and serum levels of cytokines, chemokines and growth factors. Results: We observed higher number of leucocytes, in particular lymphocytes, B lymphopenia and lower number of T regulatory cells in TET patients with associated AD compared to TET patients without AD. In the group of TET patients with AD, we also observed increased serum levels of IL-15, VEGF, IP-10, GM-CSF, IL-6, and MIP-1α. Our study describes a complex remodeling in B and T lymphocytes, highlighting differences in the T regulatory cells and modulation of relevant mediators between the two groups of patients. Conclusions: Although the pathogenic mechanisms are still unclear, our results add new knowledge to better understand the disease, suggesting the need of surveilling the immunophenotype of TET patients to ameliorate their clinical management.